A Review of Direct Z‐Scheme Photocatalysts. Issue 5 (18th April 2017) - Low, Jingxiang; Jiang, Chuanjia; Cheng, Bei; Wageh, Swelm; Al‐Ghamdi, Ahmed A.; Yu, Jiaguo
Abstract : Recently, great attention has been paid to fabricating direct Z‐scheme photocatalysts for solar‐energy conversion due to their effectiveness for spatially separating photogenerated electron–hole pairs and optimizing the reduction and oxidation ability of the photocatalytic system. Here, the historical development of the Z‐scheme photocatalytic system is summarized, from its first generation (liquid‐phase Z‐scheme photocatalytic system) to its current third generation (direct Z‐scheme photocatalyst). The advantages of direct Z‐scheme photocatalysts are also discussed against their predecessors, including conventional heterojunction, liquid‐phase Z‐scheme, and all‐solid‐state (ASS) Z‐scheme photocatalytic systems. Furthermore, characterization methods and applications of direct Z‐scheme photocatalysts are also summarized. Finally, conclusions and perspectives on the challenges of this emerging research direction are presented. Insights and up‐to‐date information are provided to give the scientific community the ability to fully explore the potential of direct Z‐scheme photocatalysts in renewable energy production and environmental remediation. Abstract : The direct Z‐scheme heterojunction is applied to enhance photocatalytic performance due to its ability to spatially separate photogenerated electron–hole pairs and optimize the redox potential of a photocatalytic system. Future development of direct Z‐scheme photocatalysts will greatly stimulate the practical application of photocatalysis in energy conversion and environmental remediation.